Hubungan Pengetahuan dengan Kepatuhan Diet pada Pasien Gagal Ginjal Kronik di Ruangan Hemodialisa RSUD UNDATA Provinsi Sulawesi Tengah : Penelitian - Moh. Syarif; Ismu Nandar Wahyu Kindang; Suaib (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Chronic kidney failure (CKF) is a progressive and permanent kidney function disorder, causing a decrease in the body's ability to maintain fluid balance. This condition has become one of the global health problems, with the incidence rate that continues to increase every year. CKF patients who undergo hemodialysis require high compliance with diet to prevent complications and maintain quality of life. However, dietary compliance is often low due to the patient's lack of knowledge about food and fluid intake management. Therefore, knowledge is an important factor that can affect the level of patient compliance in following the recommended diet. The purpose of the study is to analyze the relationship between knowledge and dietary compliance in chronic kidney failure patients in the Hemodialysis Room of the RSUD UNDATA, Central Sulawesi Province. This type of research is quantitative with a cross-sectional approach. The population is CKF patients who underwent hemodialysis of 120 people at the RSUD UNDATA in Central Sulawesi Province. The sample consisted of 55 people with the purposive sampling technique. Research instruments using knowledge and compliance questionnaires. Data analysis using the Likelihood Ratio test. The research results show that there is a relationship between knowledge and dietary compliance in chronic kidney failure patients in the Hemodialysis Room of the REUD UNDATA in Central Sulawesi Province with the results of the Likelihodd Ratio test obtained Asymp.Sig 0.001 < 0.05. There is a relationship between knowledge and dietary compliance in chronic kidney failure patients in the Hemodialysis room of the RSUD UNDATA Central Sulawesi Province. It is hoped that the hospital will strengthen the nutrition counseling program and individual counseling so that patients better understand the appropriate food and liquid intake restrictions.